Pengaruh Komposisi Kitosan Terhadap Sifat Biodegradasi dan Water Uptake Bioplastik dari Serbuk Tongkol Jagung - Muhammad Nur Alam; Kumalasari Kumalasari; Nurmalasari Nurmalasari; Ilmiati Illing (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2018)
The aim of this research is to obtain the effect of chitosan addition on the properties of biodegradation and water uptake for bioplastics. Bioplastic is made from mixing corncob powder and chitosan using by gliserol as plasticizer. Bioplastic is synthesized for gelatinization temperature of 80oC. Chitosan addition is varied to 2, 4, and 6 g. Based on the analysis, the addition of chitosan can significantly decrease water uptake of bioplastic. The lowest percentage of water uptake was 8.59 % by addition 6 gr chitosan. The highest weight loss percentage of bioplastic was 88,42 % which is obtained by the addition of 2 gr chitosan heaped for 15 days in soil. This indicates that the bioplastic has the high biodegradation properties. Also, the result of FTIR analysis indicated presence of O-H and N-H groups of bioplastics due to the addition of chitosan and glyserol, but their instensity experienced falling down and shifting at the wave numbers after stockpiled.